John Bull’s proconsuls: military officers who administered the British Empire, 1815-1840 - Smith, Robert J. (Kansas State University, 2008)
At the conclusion of the Napoleonic Wars, Britain had acquired a vast empire that included territories in Asia, Africa, North America, and Europe that numbered more than a quarter of the earth's population. Britain also possessed the largest army that the state had ever fielded, employing nearly 250,000 troops on station throughout this empire and on fighting fronts in Spain, southern France, the Low Countries, and North America. However, the peace of 1815 and the end of nearly twenty-five years of war with France brought with it significant problems for Britain. Years of war had saddled the state with a massive debt of nearly £745,000; a threefold increase from its total debt in 1793, the year war with the French began. Furthermore, the rapid economic changes brought on by a the state that had transitioned from a wartime economy to one of peacetime caused widespread unemployment and financial dislocation among the British population including the thousands of officers and soldiers who had fought in the Napoleonic Wars and were now demobilized and back into the civilian sector. Lastly, the significant imperial growth had stretched the colonial administrative and bureaucratic infrastructure to the breaking point prompting the Colonial Office and the ruling elites to adopt short-term measures in running its empire. The solution adopted by the Colonial Office in the twenty-five years that followed the Napoleonic Wars was the employment of proconsular despotism. Proconsular despotism is the practice of governing distant territories and provinces by politically safe individuals, most often military men, who identified with and were sympathetic to the aims of the parent state and the ruling elites. The employment of this form of colonial governance helped to alleviate a number of problems that plagued the Crown and Parliament. First, the practice found suitable employment for deserving military officers during a period of army demobilization and sizeable reduction of armed forces. The appointment of military officers to high colonial administrative positions was viewed by Parliament as a reward for distinguished service to the state. Second, the practice enabled Colonial Office to employ officials who had both previous administrative and military experience and who were accustomed to make critical decisions that they believed coincided with British strategic and national interests. Third, the employment of knowledgeable and experienced army officers in colonial posts fulfilled the Parliamentary mandates of curtailing military spending while maintaining security for the colonies. Military officers of all ranks clamored for the opportunities of serving in the colonies. General and field grade officers viewed service in the colonies as a means of maintaining their status and financially supporting their lifestyles. Company grade officers, who primarily came from the emerging middle class, saw colonial service as a means of swift promotion in a peacetime army and of rising socially. Competition for overseas administrative positions was intense and officers frequently employed an intricate and complex pattern of patronage networking. The proconsular system of governing Britain's vast network of colonies flourished in the quarter century following the Battle of Waterloo. In the immediate aftermath of the Napoleonic Wars the British officer corps contributed men who became the principal source for trained colonial administrators enabling Britain to effectively manage its immense empire.
Keywords: British; imperial; history; History, European (0335)